DEVELOPMENT OF THE ALGEBRA MODULES FOR CLASS VII STUDENTS - Diska Puri Dewi; Abdul Taram (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Mathematics is an essential basic science and useful for the development of science and technology. Available teaching materials limit the use of teaching materials in the schools. Algebra material is still considered difficult for some students'. Instructional materials in the form of modules are expected to become facilities that support the learning process. This research aims to produce teaching materials in mathematic modules with the algebra materials in the Junior High School student class VII. This research development using ADDIE that is Analysis, Design, Development, Implementation, Evaluation. This study's subjects are the materials experts, media experts, and State Junior High School (SMP Negeri) 2 Gamping Sleman and Junior High School (SMP) Muhammadiyah 2 Gamping Sleman. The instrument of this research is a questionnaire. The analysis data use the qualitative and quantitative techniques to calculate the result score of feasibility in learning media development. The result of the development of teaching materials in the form of module based on the quality of each aspect in the learning media in terms of experts materials with very good category with an average score of 81, in terms of media experts with good category with an average score of 69.33, and student response with very good category with an average score of 37.81. Based on the assessment, the teaching materials in the form of the module are very suitable for learning.